National Resident Matching Program Rank Order and Performance in an Internal Medicine Residency. Issue 10 (October 2021) - Everett, George D.; Maharam, Edward; Yi, Fanchao
Abstract : The authors studied a 5-year cohort of 56 Internal Medicine residents at a large, urban, quaternary medical center to evaluate the relationship between objective preresidency predictor (National Resident Matching Program [NRMP] rank, US Medical Licensing Examination score, age, sex, medical school grades and type, immigration status, and added qualifications) and end-residency outcome (faculty ranking, Accreditation Council for Graduate Medical Education Milestones, National In-Training Examination scores, Fellowship and Chief Resident attainment) variables of residency training. The main hypothesis was that better NRMP rank predicted better outcomes, a hypothesis not previously evaluated in an Internal Medicine residency. Multivariable analysis revealed that US Medical Licensing Examination score was the best predictor of favorable outcome for milestones, faculty ranking and National In-Training Examination scores. NRMP rank showed only limited predictive ability for milestones outcome. Fellowship and chief resident attainment was not predictable by any combination of variables. Abstract : Objectives: Prospective first-year house staff and residency program leaders spend substantial time, effort, and expense preparing a rank order list for the National Resident Matching Program (NRMP). Previous studies have mostly shown minimal or no relation between rank order and subsequent resident performance, raising questions about the value of this process. Furthermore, no previous studies have been done with Internal Medicine residencies. As such, the purpose of this study was to compare NRMP rank order to multiple objective outcomes of an Internal Medicine residency. Methods: A retrospective cohort of Internal Medicine residents from five consecutive graduating classes, trained between July 1, 2013 and July 31, 2020, were evaluated for five objective outcomes: Accreditation Council for Graduate Medical Education (ACGME) milestones, faculty rankings of quality, National In-Training Examination scores, chief resident attainment, and fellowship attainment. Outcomes were analyzed in relation to eight potential predictors: NRMP rank, medical school type and grades, immigration status, added qualifications, sex, age and US Medical Licensing Examination (USMLE) scores, using univariate and multivariate analyses. Results: From a cohort of 61 residents, 56 were eligible. All eligible residents' data were included, for a participation rate of 100% (56 of 56). There were no statistically significant univariate or multivariate predictors for the endpoint of fellowship attainment. Higher USMLE scores were predictive of chief resident status in univariate analysis only. NRMP rank was significantly correlated with ACGME milestones in the univariate analysis. The multivariate analysis revealed that higher USMLE score was statistically significantly predictive of more favorable milestones, faculty ranking, and National In-Training Examination score. Conclusions: Higher USMLE score was statistically significantly associated with multiple favorable objective residency outcomes in an Internal Medicine residency. A better NRMP rank was correlated with favorable ACGME milestones in univariate analysis, but USMLE score emerged as the strongest predictor in multivariate analysis.